2017
DOI: 10.1016/j.electacta.2017.07.157
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of new quaternary ZrNbTiAl alloys in simulated physiological solution using electrochemical techniques and surface analysis methods

Abstract: The potential biomedical application of three new quaternary Zr alloys, namely Zr6Ti15Nb4Al, Zr32Ti15Nb4Al, and Zr49Ti15Nb4Al, was evaluated in vitro using electrochemical methods complemented with surface analysis of corrosion resistance. Cyclic potentiodynamic polarization (CCP) and electrochemical impedance spectroscopy (EIS) tests were performed in Ringer's solution at 37 ºC. The electrochemical behavior of the ZrTiNbAl quaternary alloys was consistent with the formation of passivating oxide films on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The Mg-0.5Ca-xY alloy was developed using controlled atmosphere induction melting equipment from "Gh. Asachi" Technical University of Iasi, Faculty of Materials Science and Engineering [18,19]. The metallic loading was performed for about 15 grams of Mg-0.5Ca-xY (x= 1 wt% Y, 2 wt% Y, respectively 3 wt%Y) alloy in cylindrical crucibles having a diameter of 20 mm and a height of 40 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The Mg-0.5Ca-xY alloy was developed using controlled atmosphere induction melting equipment from "Gh. Asachi" Technical University of Iasi, Faculty of Materials Science and Engineering [18,19]. The metallic loading was performed for about 15 grams of Mg-0.5Ca-xY (x= 1 wt% Y, 2 wt% Y, respectively 3 wt%Y) alloy in cylindrical crucibles having a diameter of 20 mm and a height of 40 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The relatively rough porous characteristics increase the effective surface area exposed to the solution and the inhomogeneous elements distribution interrupt the stability of the passivating oxide film. In the high positive potential, the preexisting passivation might be ruptured and the non-oxidized area could be corroded, 8 so the corrosion current increases consequentially and finally another higher passive film is created.…”
Section: Resultsmentioning
confidence: 99%
“…Zr-containing Ti alloys have been developed for commercial biomaterials. [8][9][10][11][12] It is reported that the elastic modulus of a near β-type Ti-Nb-Zr alloy at room temperature are about [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] GPa if the alloy composition and heat-treatment conditions are optimized. 10,13,14 This value is close to the elastic modulus of human bones and it is conducive to reducing the stress shielding between natural bones and implants.…”
mentioning
confidence: 99%
“…Zirconium is mainly used as a structural material in nuclear applications due to its low absorption of neutrons. Recently, zirconium-based materials have gained attention as structural materials for aerospace, chemical and biomedical applications because of their resistance against corrosion and wear [1]. The combination of acceptable strength, high corrosion resistance and good biocompatibility has made zirconium alloys suitable for biomaterials for orthopedic implants.…”
Section: Introductionmentioning
confidence: 99%